A Modular Compliant Actuator for Emerging High Performance and Fall-Resilient Humanoids - F. Negrello; M. Garabini; M. G. Catalano; J. Malzahn; D. G. Caldwell; A. Bicchi; N. G. Tsagarakis (15th IEEE RAS Humanoids Conference (HUMANOIDS2015), 2016)
This work is supported by the WALK-MAN FP7-ICT-2013-10 European Commission project.
Keywords: Robotics

Manipulation Framework for Compliant Humanoid COMAN: Application to a Valve Turning Task - A. Ajoudani; J. Lee; A. Rocchi; M. Ferrati; E. Mingo Hoffman; A Settimi; D. G. Caldwell; A. Bicchi; N G Tsagarakis (IEEE-RAS International Conference on Humanoid Robots (HUMANOIDS 2014), 2014)
With the purpose of achieving a desired interaction performance for our compliant humanoid robot (COMAN), in this paper we propose a semi-autonomous control framework and evaluate it experimentally in a valve turning setup. The control structure consists of various modules and interfaces to identify the valve, locate the robot in front of it and perform the manipulation. The manipulation module implements four motion primitives (Reach, Grasp, Rotate and Disengage) and realizes the corresponding desired impedance profile for each phase to accomplish the task. In this direction, to establish a stable and compliant contact between the valve and the robot hands, while being able to generate the sufficient rotational torques depending on the valve's friction, Rotate incorporates a novel dual-arm impedance control technique to plan and realize a task-appropriate impedance profile. Results of the implementation of the proposed control framework are firstly evaluated in simulation studies using Gazebo. Subsequent experimental results highlight the efficiency of the proposed impedance planning and control in generation of the required interaction forces to accomplish the task.
Keywords: Haptics; Robotics